The frequency and persistence of lymphedema diagnosis and self-reported symptoms over 5 years in patients with endometrial carcinoma - Julia Ritchie; Quetrell Heyward; Nicholas Taylor; Emily Ko; Ashley F. Haggerty; Ashley Graul (Elsevier, 2022)
A potentially debilitating sequela of diagnosis or treatment for endometrial cancer islower limb lymphedema (LLL), which can have significant impacts on quality of life. Theobjective of this study was to determine the frequency of LLL symptoms in uterinecancer survivors over a 5-year study period. An IRB-approved prospective study of quality of life of endometrial cancer patients whounderwent surgical intervention was undertaken. The Gynecologic CancerLymphedema Questionnaire (GCLQ) was used to survey patients in 2011 and again in2016 to evaluate for symptoms of LLL.205 patients initially answered the survey, and 75 patients completed the follow upsurvey as well, with no differences in demographics between the cohorts. 90.7% ofpatients underwent lymph node dissection. Patients commonly reported symptoms ofnumbness (66.83%), aching (54.2%), and poor physical function (47.8%). On initialsurvey, 14.7% (n = 11) of patients met criteria for LLL by GCLQ criteria, with 8 patientsreporting improvement in symptoms and 3 reporting persistent diagnosis at follow up. At follow up survey, 12.0% (n = 9) patients meeting criteria five years later, with 6patients newly meeting criteria. The most persistent symptoms were poor physicalfunction (70.6%), numbness (72.5%), general swelling (55.6%), aching (64.1%), andlimb-related swelling (60%).While the rate of LLL was similar to previous reports, there were a number of newdiagnoses of LLL at interval follow up distant from surgery, up to 7 years later.Symptoms of LLL also persisted for many years after diagnosis.